Architecture Competition: Argentine Industrial Union Building of the (1968): Cultural representations, theory production and transformation of space. (ARQUISUR Revista, 2021)
This article inquires about the five (5) first prizes of the architecture competition for the new building of the Unión Industrial Argentina (UIA), held in Argentina in 1968. Within the framework of the developmetalism ideology, during post- war period, there was an architecture competition boom, primarily promoted by the State, but also by the private area. In this way, we consider the competition practice, and the increase in its use in the 1960s, as a vehicle that indicates and generates innovation, rupture and transformation in the ways of space production, and later, verified the opposition of an old and a new way of making architecture. Through the interpretation and micro analysis of the awarded projects, we address the visual documents as primary sources that, on one side, act as representations of the architecture culture as symbolic and material culture within an specific context, and on the other hand, they enable a multiplicity of readings that allow to verify the displacement in the ways of production of the disciplinary space.
Keywords: architecture, architecture competitions, developmentalism, images, micro–history.